The Effect of Corporate Social Responsibility to Corporate Profitability (ROA) and Stock Return - Hakim, Hilmi Farizan; Nugroho, Anggoro Budi (Journal of Business and Management, 2014)
– This research objective is to find out the impact of Corporate Social Responsibility (CSR) expense towards company profitability (ROA) and stock return in each different business sectors. This research used purposive sampling to select the companies. The company that became the sample in this study is LQ 45 companies listed on the Indonesia Stock Exchange period Q1 2009 to Q1 2014, the best nine companies in different business sectors, both private and state-owned enterprises (SOEs). Data used in this study is the documentary data, quarterly financial reports of the company. Study took data from the best LQ 45 Company in each sector during the study period. In this study, there are two dependent variables and one independent variable. The dependent variables are profitability (ROA) and stock return. The independent variable is CSR expense. The results of this research are: (1.) CSR expense has a positive significant effect toward profitability (ROA) in six companies (LSIP, INTP, ASII, UNVR, PGAS, and BMRI), has a negative significant effect toward profitability (ROA) in three companies (PTBA, LPKR, and UNTR), (2.) CSR expense has a positive significant effect toward stock return in all nine companies (LSIP, INTP, PTBA, ASII, UNVR, LPKR, PGAS, BMRI and UNTR).Keywords: Corporate Social Responsibility, Profitability, Return on Assets, Stock Return